Effect of salicylic acid during heavy metal stress - Pál, Magda (Acta Biologica Szegediensis, 2002)
The effect of salicylic acid (SA) on Cd-induced stress was investigated in young maize (hybrid Norma) plants. When SA and Cd were applied simultaneously, the damage was less pronounced than without SA. However, SA treatment itself also caused oxidative stress and damage to the root system, and inhibited the phytochelatin synthase enzyme, so when the SA treatment was used before the Cd stress, it accelerated the damaging effect.